Owner compliance with medication administration in small animal practice in New Zealand : a dissertation submitted in fulfilment off the requirements for the degree of Master of Veterinary Science in the School of Veterinary Science, Massey University, Palmerston North, New Zealand - Odom, Thomas F. (Massey University, 2023)
Medication compliance is a critical aspect of veterinary care for both cats and dogs. Despite its importance, research suggests that non-compliance is a common problem in veterinary medicine. Understanding the factors that influence medication compliance in cats and dogs is crucial for improving veterinary care and ultimately, the health and wellbeing of these animals. In this thesis, the various factors that impact medication compliance in these pets will be explored. Presented here are the results of a cross-sectional survey of cat and dog owners, investigating their demographic data and their opinions on medicating their pets. Chapter 2 of the thesis is a review of the current literature relating to medication compliance in small animal practice and its importance within the greater context of human medicine. Chapters 3 and 4 represent two original investigations to characterize medication compliance in cats and dogs in New Zealand. These chapters have been written in the format of manuscripts for peer review and publication. These are titled: Prescribing oral antibiotics for home administration by clients to their cats is associated with medication non-compliance and Factors associated with medication non-compliance in dogs. Chapter 5 discusses the overall findings, the implication the findings have for medication compliance within New Zealand and future research options.
Keywords: 300911 Veterinary pharmacology